Characteristics and Outcomes of Staphylococcus aureus Bloodstream Infection Originating From the Urinary Tract: A Multicenter Cohort Study. (6th June 2020) - Grillo, Sara; Cuervo, Guillermo; Carratalà, Jordi; Grau, Immaculada; Llaberia, Mariona; Aguado, José María; Lopez-Cortés, Luis Eduardo; Lalueza, Antonio; Sanjuan, Rafael; Sanchez-Batanero, Ana; Ardanuy, Carmen; García-Somoza, Dolors; et al.
Abstract: Background: Staphylococcus aureus bloodstream infection (SABSI) arising from a urinary tract source (UTS) is poorly understood. Methods: We conducted a retrospective analysis in 3 major teaching hospitals in Spain of prospectively collected data of hospitalized patients with SABSI. SABSI-UTS was diagnosed in patients with urinary tract symptoms and/or signs, no evidence of an extra-urinary source of infection, and a urinary S. aureus count of ≥10 5  cfu/mL. Susceptibility of S. aureus strains and patient mortality were compared between SABSI from UTS (SABSI-UTS) and other sources (SABSI-other). Results: Of 4181 episodes of SABSI, we identified 132 (3.16%) cases of SABSI-UTS that occurred predominantly in patients who were male, had high Charlson comorbidity scores, were dependent for daily life activities, and who had undergone urinary catheterization and/or urinary manipulation before the infection. SABSI-UTS was more often caused by MRSA strains compared with SABSI-other (40.9% vs 17.5%; P < .001). Patients with SABSI-UTS caused by MRSA more often received inadequate empirical treatment compared with those caused by susceptible strains (59.7% vs 23.1%; P < .001). The 30-day case fatality rate was lower in patients with SABSI-UTS than in those with SABSI-other (14.4% vs 23.8%; P = .02). Factors independently associated with mortality were dependence for daily activities (aOR, 3.877; 95% CI, 1.08–13.8; P = .037) and persistent bacteremia (aOR, 7.88; 95% CI, 1.57–39.46; P = .012). Conclusions: SABSI-UTS occurs predominantly in patients with severe underlying conditions and in those who have undergone urinary tract manipulation. Moreover, it is frequently due to MRSA strains and causes significant mortality.